Reporting Systems in Public Administration: The New Approach for Austrian Universities - Michaela Schaffhauser-Linzatti (Central European Public Administration Review)
Together with the reorganisation of public administration, reporting on public performances is steadily becoming more transparency and process efficiency orientated. Various levels of reporting are being acquired, depending on the stakeholders concerned, comprising internal, inter-bureaucratic, and external information systems. Taking Austrian universities as an example, this article shows the advantages and pitfalls present when such reporting systems are “borrowed” from private applications without adapting them to public necessities. It focuses on the Austrian university intellectual capital statement as one of the most important reports using intangible values in the light of theoretical criteria and practical experience.